THE ROCK-COAL BOUNDARY CONTROL METHODS SUBSTANTIATION FOR COAL MINING COMBINES - Kaganiuk, Oleksii; Melnyk, Vasyl; Polishchuk, Mykola; Hryniuk, Serhii; Bortnyk, Kateryna (Proceedings of National Aviation University (archive), 2019)
The issue of diagnostics provided by modern methods is considered in this paper to control the rock-coal boundary that are based on the application of various sensors and approaches. A detailed analysis for the various methods results is presented to control the rock-coal boundary that, in particular, are based on the differences in the coal and rock cuttingresistance, the method of using the differences between the elastic properties of rock and coal and their friction coefficients, and the ultrasonic method. All of them are related to the diagnostic methods with the open boundary of the rock-coal section. There also is emphasizeda necessity of new sensors creation for controlling the coal and rock boundary for combines operated in mining conditions. It is revealed that from the introduction into operation in mine conditions point of view, the most promising is the radioisotope small-sized sensors, which allow to control the boundary of the section between coal and rock in a contactless manner. Other monitoring methods that are being considered in this paper cannot be implemented in the without-human process of coal minning, but they can play an important role to create some other interesting directions and new methods for controlling the boundary between the rock and coal that will allow the creation of automatic control systems for coal-mining combines working in difficult minning conditions.